1990
DOI: 10.1007/bf00053441
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled crossover study of ketanserin in elderly hypertensive patients

Abstract: The results of the European Working Party for Hypertension in the Elderly Study showed that treatment of high blood pressure reduced the morbidity and mortality from strokes and myocardial infarction and reduced the incidence of heart failure in elderly patients. The largest number of hypertensive patients are elderly, and it is in this group of patients that the maximum benefit of treatment might be expected. The present study was designed to study in detail the efficacy and tolerability of ketanserin in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…28 In a previous crossover study, differences in quality of life scores between ketanserin and placebo have been obtained with only 17 patients. 32 In the present study, efficacy analysis was performed on 61 patients. Quality of life trials should last sufficiently long, 4,28 in order to allow for adaptation to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…28 In a previous crossover study, differences in quality of life scores between ketanserin and placebo have been obtained with only 17 patients. 32 In the present study, efficacy analysis was performed on 61 patients. Quality of life trials should last sufficiently long, 4,28 in order to allow for adaptation to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have been reported on the influence of ketanserin on quality of life in older hypertensives (McCarthy et al 1990;Meyer & Safar 1988). The first was a comparative study involving a novel placebo-controlled crossover design: despite the fact that only 17 patients were enrolled, a striking difference appeared in the overall quality of life score between the patients receiving ketanserin and those in the placebo phase, and the results were independent of treatment sequence.…”
Section: Other Antihypertensive Agentsmentioning
confidence: 96%